"Industry in a Global City...Who cares, we need land! - Mijares Chavez, Patricia (Premio Internacional de tesis de investigación 2017. Transformación urbana. Densidad habitacional y ciudad compacta, 2017)
The overarching aim of this research is to understand in what ways the planning policy is being implemented to protect or release industrial land uses in London in order to pursue a Global City vision, within a compact city model, while choosing the area of Park Royal, located in North West London, as a case study. The case study is used to analyse how the policy would protect a specific industrial land that is justified as strategic for the London economy.